Ionizing radiation improves skin bacterial dysbiosis in cutaneous T-cell lymphoma - Chrisman, Lauren P.; Pang, Yanzhen; Hooper, Madeline J.; Rajeev-Kumar, Greeshma; Nguyen, William Q.; Green, Stefan J.; Seed, Patrick C.; Liang, Hua; Mittal, Bharat B.; Hasan, Yasmin; Guitart, Joan; Weichselbaum, Ralph R.; et al. (Frontiers in Immunology, 2024)
IntroductionCutaneous T-cell lymphoma (CTCL) is closely associated with the host microbiome. While recent evidence suggests that shifts in specific bacterial taxa are associated with response to UV-B, a form of non-ionizing radiation, the impact of ionizing radiation (IR) has not been investigated.Methods16S rRNA and tuf gene amplicon sequencing were performed on DNA extracted from swabs of lesional/non-lesional skin of 12 CTCL patients before/after TSEBT or local IR and from 25 matched healthy controls (HC). Microbial diversity and taxonomic profiles were analyzed.ResultsRadiation exposure increased CTCL skin α-diversity to levels approximating HC. TSEBT appeared to carry the greatest effect compared to local IR. Both α and β-diversity differed significantly post versus pre-IR for TSEBT, but not for local IR. IR was associated with decreases in known pathogenic bacteria such as Streptococcus and S. aureus and increases in healthy commensal bacteria such as Anaerococcus, Bifidobacterium and commensal staphylococci including S. pettenkoferi. Substantially more taxa shifts were seen with TSEBT versus local IR.DiscussionIR not only eliminates CTCL lesions via induction of apoptosis, but also facilitates skin barrier restoration and recolonization of bacterial taxa associated with a healthy skin microbiome. Local IR does not have as strong an effect on the skin microbiome as TSEBT. As skin microbiota act as immunomodulators with local and potentially systemic influence, TSEBT may also improve CTCL lesions via global effects on the skin microbiome. Future larger-scale studies are required to fully elucidate the relationship between cutaneous microbes and IR treatment in CTCL.